2021
DOI: 10.1088/1757-899x/1013/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Machine Learning algorithms for Intrusion Detection

Abstract: In this modern era, the network related applications, programs and services are growing enormously but the network security issues also grow along with them. Keeping the network secure is a challenging and a crucial task. To maintain the secure network there must be some system which can detect and identify any malicious activity happening in network. This system is called as Intrusion Detection System. There are many traditional network security tools and techniques of preventing intrusion like firewalls, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Table 3.1. Illustrate the Distribution of instances in NSL-KDD dataset for training and testing [23]. Each instance in the dataset displays 41 continuous and discrete attributes (38 numerical and 3 symbolic), to more details [24,25].…”
Section: Datasetsmentioning
confidence: 99%
“…Table 3.1. Illustrate the Distribution of instances in NSL-KDD dataset for training and testing [23]. Each instance in the dataset displays 41 continuous and discrete attributes (38 numerical and 3 symbolic), to more details [24,25].…”
Section: Datasetsmentioning
confidence: 99%
“…Supervised ML algorithms are widely used in computer network traffic analysis. The performance evaluation and comparative analysis of supervised ML used in classification are presented in [11,[27][28][29][30][31][32].…”
Section: Related Workmentioning
confidence: 99%
“…However, since the differences were small, the authors concluded that either model could be used. Performance evaluation and comparative analysis of FNN, SVM, DT, k-NN and wk-NN classifiers can be found in [3,17,28,[31][32][33][34][35][36][37][38][39][40].…”
Section: Related Workmentioning
confidence: 99%
“…In order to determine the statistical model of an anomalybased IDS, various approaches used a number of assumptions about the training data and validation methods. To classify network traffic, the authors of [6][7][8][9] present a comparative analyses and performance evaluation of multiple supervised ML algorithms. The most widely used supervised ML models including SVM [3][4][5], Naïve Bayes (NB) [6,7], DT [7,8], nearest neighbors [9][10][11], random forest (RF) [6,7,12], artificial neural networks (ANN) [7,10,13], logistic regression (LR) [6,7], discriminant analysis (DA) [9], and ensemble methods (EM) [14][15][16] were analyzed.…”
Section: Introductionmentioning
confidence: 99%